Ka mua, ka muri : exploring mātauranga Māori foundations for healing traumatic brain injury : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, New Zealand - Kahika-Foote, Tania (Massey University, 2025)
Globally, traumatic brain injury (TBI) is the leading cause of long-term disability and injury-related death. In Aotearoa New Zealand, TBI disproportionately affects Māori, yet contemporary neurorehabilitation settings remain grounded in Western biomedical frameworks. These frameworks inadequately reflect Māori understandings of healing and well- being, often rendering cultural identity as invisible. This thesis explores how mātauranga Māori (Māori knowledge) understandings of injury trauma and brain health inform healing pathways for Māori with TBI. Grounded in Kaupapa Māori Research methodology, this study employed a dual-method approach that combined archival research with semi-structured interviews. Archival research was undertaken through a culturally guided, iterative process that engaged trusted repositories of mātauranga Māori to examine ancestral teachings relating to injury trauma and the brain. Semi-structured interviews were conducted with Māori health professionals enabling an in depth exploration of TBI from those who navigate both clinical contexts and Māori cultural paradigms. Analytical rigour was maintained through a six-step process that wove together Pūrākau and Ara Wairua as complementary analytical frameworks ensuring coherence with Māori ontologies and ethical commitments. The findings, were presented across three analytical chapters, culminating in a synthesising discussion that advanced three interconnected theoretical propositions. First, it is fundamental that TBI rehabilitation is centred around understandings of tapu (sacredness), wairua (spiritual), and mauri (life force). Second, the brain carries whakapapa (lineage), it embodies cosmological connections, ancestral knowledge and sociocultural lineages that shape both vulnerability to injury and pathways of recovery and resilience. Third, for ethical and culturally safe neurorehabilitation practice, the study calls for pedagogical shifts and neuro-health professionals to champion the integration of mātauranga Māori within clinical spaces, enabling practices that uphold the sanctity of the upoko (head) and support whānau-centred (family) healing.
Keywords: Māori Masters Thesis; 451009 Ngā rongoā me ngā whakamaimoa o te Māori (Māori medicine and treatments); 451013 Mātauranga hinengaro kaupapa Māori (Māori psychology)